2017
DOI: 10.1039/c7md00227k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in combretastatin based derivatives and prodrugs as antimitotic agents

Abstract: The dynamic and crucial role of tubulin in different cellular functions rendered it a promising target in anticancer drug development. Combretastatin A-4 (CA-4), an inhibitor of tubulin polymerization isolated from natural sources, is a lead molecule with significant cytotoxicity against tumour cells. Owing to its non polar nature it exhibits low solubility in natural biological fluids, thereby prompting the development of new CA-4 based derivatives. The modification of this lead molecule was mostly carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 71 publications
0
48
0
7
Order By: Relevance
“…[8,9] To avoid this isomerization problem, a large number of stable CA-4 analogs have been synthesized by including the double bond in heterocycle. [10,11,12] In 2005 our group initiated a medicinal chemistry program to prepare stable analogues of CA-4 by replacing the (Z)-ethylene double bond with various non-isomerizable spacers having different sizes (from 1 to 6 carbon atoms). [13,14,15,16] In 2007, [17] we resolved the stability problem of CA-4 by finding and demonstrating that isoCA-4, [18,19] the stable and non-natural isomer of CA-4 having a 1,1-diarylethylene structure, had the same biological properties as the natural product ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] To avoid this isomerization problem, a large number of stable CA-4 analogs have been synthesized by including the double bond in heterocycle. [10,11,12] In 2005 our group initiated a medicinal chemistry program to prepare stable analogues of CA-4 by replacing the (Z)-ethylene double bond with various non-isomerizable spacers having different sizes (from 1 to 6 carbon atoms). [13,14,15,16] In 2007, [17] we resolved the stability problem of CA-4 by finding and demonstrating that isoCA-4, [18,19] the stable and non-natural isomer of CA-4 having a 1,1-diarylethylene structure, had the same biological properties as the natural product ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…It is vital for tubulin binding and binding at the colchicine binding site of the microtubule [110]. Structure−activity relationship (SAR) studies showed that features, such as (i) cis-orientation of both the aromatic rings, (ii) the 3,4,5-trimethoxy moiety on ring A, and (iii) the para-methoxy moiety present on ring B, are important for CA-4 cytotoxic activity [111]. It was found that several antimitotic agents, such as combretastatin A-4, colchicine, steganacin, and podophyllotoxin, may bind at the colchicine site on tubulin due to the presence of trimethoxy aryl unit [112].…”
Section: Combretastatins-between Bench and Bedsidementioning
confidence: 99%
“…However, replacement of trimethoxy group with chlorine, fluorine, incorporation of big size groups also has resulted in favourable retention of activity and potency. [20,45] The spatial arrangement of the 'ethylene-bridge' is also vital as the cis form of CA-4 is found thermodynamically more stable at the CBS. The molecule CA-4 moves to CBS site through the interface of the α-β chain of tubulin in a way that it interrupts interaction of Guanosine-5'-triphosphate (GTP) (present at the T5-loop of the α-chain of tubulin).…”
Section: Introductionmentioning
confidence: 99%
“…[21,46] In the 'Bring' portion ( Figure 2), different functional group substitution on the aromatic ring, complete replacement of substituted benzene ring with the aliphatic group is being experimented in the present work. [20,[45][46][47] Both heterocyclic moieties, isoxazoline and triazole, were incorporated in place of 'ethylene-bridge' of CA-4 in the present work which will enhance the structure's overall surface area with interactions may enhance towards βsubunit of CBS. [20,27,29,39,[48][49][50][51] The Result & Discussion…”
Section: Introductionmentioning
confidence: 99%